The Role of Institutions and Community Empowerment in Realizing Sustainable Tourism in Bakas Village, Klungkung District - Made Dian Putri Agustina; I Made Astrama; Putu Putra Astawa; I Gusti Ayu Wimba; A. A. Ngurah Gede Sadiartha (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
This study aims to identify the role of institutions and community participation in tourism development in Bakas Tourism Village. This study uses quantitative and qualitative approaches. This study was conducted by observing and digging up information directly about the role of institutions and community empowerment in realizing sustainable tourism through previously prepared study instruments. Based on the results, it revealed that the role of institutions is very active in the management of Bakas Tourism Village. In addition, community participation is also active in the development of Bakas Tourism Village from the planning stage to supervision.